ANALISIS KONTRIBUSI EKSISTENSI MADRASAH IBTIDAIYAH TERHADAP INDEKS PEMBANGUNAN MANUSIA DI JAWA TIMUR - Ulfah Muhayani; Prayudi Lestantyo; Abd. Rahman Ambo' Dalle; Sutrisno Sutrisno (STKIP Pesisir Selatan, 2026)
Objective: This study analyzes the contribution of the existence of Madrasah Ibtidaiyah (MI) to the Human Development Index (HDI) in East Java through an interprovincial comparative approach. The study is grounded in the fact that MI represents one of the largest Islamic primary education institutions and is widely distributed across East Java. Despite its extensive presence, limited research has examined its contribution to human development. Methods The research data were obtained from Statistics Indonesia (BPS), covering the number of MI institutions and provincial HDI achievements in 2025. This study employed a quantitative descriptive-comparative approach, with data analyzed using Microsoft Excel through tabulation, ranking, and interprovincial comparative analysis. Results: The findings reveal that a large number of MI institutions does not necessarily correspond to a higher HDI. East Java, which has the largest number of MI institutions in Indonesia, ranks only 12th in the national HDI ranking. In contrast, several provinces with relatively fewer MI institutions, such as the Special Capital Region of Jakarta, the Special Region of Yogyakarta, and the Riau Islands, have achieved higher HDI scores. These findings indicate that human development is influenced not only by the quantity of educational institutions but also by educational quality, health conditions, economic circumstances, basic infrastructure, and the effectiveness of regional development governance.